Ferroptosis and Acute Kidney Injury (AKI): Molecular Mechanisms and Therapeutic Potentials - Feng, Qi; Yu, Xiaoyue; Qiao, Yingjin; Pan, Shaokang; Wang, Rui; Zheng, Bin; Wang, Hui; Ren, Kai-Di; Liu, Hui; Yang, Yang (Frontiers in Pharmacology, 2022)
Acute kidney injury (AKI), a common and serious clinical kidney syndrome with high incidence and mortality, is caused by multiple pathogenic factors, such as ischemia, nephrotoxic drugs, oxidative stress, inflammation, and urinary tract obstruction. Cell death, which is divided into several types, is critical for normal growth and development and maintaining dynamic balance. Ferroptosis, an iron-dependent nonapoptotic type of cell death, is characterized by iron overload, reactive oxygen species accumulation, and lipid peroxidation. Recently, growing evidence demonstrated the important role of ferroptosis in the development of various kidney diseases, including renal clear cell carcinoma, diabetic nephropathy, and AKI. However, the exact mechanism of ferroptosis participating in the initiation and progression of AKI has not been fully revealed. Herein, we aim to systematically discuss the definition of ferroptosis, the associated mechanisms and key regulators, and pharmacological progress and summarize the most recent discoveries about the role and mechanism of ferroptosis in AKI development. We further conclude its potential therapeutic strategies in AKI.